Seasonal effects on the semen production of Bali bulls (Bos javanicus) in West Nusa Tenggara's Lelede regional artificial insemination center - Tulus Maulana; Saiful Anwar; Slamet Diah Volkandari; Muhammad Nur; Syahruddin Said (Livestock and Animal Research, 2022)
Objective: The purpose of this research is to determine the effect of the rainy and dry seasons on the sperm qualities and frozen sperm production of Bali bulls at the Lelede Regional Artificial Insemination Center (RAIC) in West Nusa Tenggara.Methods: A total of 1226 ejaculates were examined from five Bali bulls during a 24-month period (November 2018–October 2019), which was classified into rainy (November–April, 658 ejaculates) and dry (May–October, 568 ejaculates) seasons. Semen volume (mL), sperm velocity (1-4), motility (%), concentration (x106 cell/ml), pre-freezing motility (%), post-freezing motility (%), recovery rate (%), and total frozen semen production were examined as sperm quality measures.Results: The results indicated that during the rainy season, ejaculates and processed sperm were more abundant than during the dry season. Additionally, the features of discarded fresh semen in the volume parameter were significantly (P<0.05) larger during the dry season than during the rainy season. The pattern in semen output rises during the dry season and decreasing during the rainy season.Conclusions: It was concluded that the rainy season results in a higher number of ejaculates and total sperm production than the dry season. Meanwhile, no differences in sperm characteristics exist between the two seasons.